D-106 Cellular immune correlates analysis of an HIV-1 pre- exposure prophylaxis trial. (January 2016) - Kuebler, Peter; Mehrotra, Megha; McConnell, Jeff; Holditch, Sara; Shaw, Brian; Tarosso, Leandro; Leadabrand, Kaitlyn; Milush, Jeffrey; York, Vanessa; Raposo, Rui Andre Saraiva; Cheng, Rex; Eriksson, Emily; et al.
Abstract : The majority of HIV exposures do not result in an established systemic infection. Preexposure Prophylaxis (PrEP) trials provide the right subjects with sufficient numbers to investigate mechanisms of resistance. We leveraged the global iPrEx PrEP trial to query T cell mediated mechanisms of resistance. We compared those who remained HIV-1 seronegative (HESN) to those who became infected during the trial with the variables of HIV-specific IFN-γ T cell responses, frequency and phenotypes of activated T cells and HLA MHC class I genotypes. HIV-specific IFN-γ responses were more frequent in HESN when compared to matched pre-infection samples from those who became infected. Logistic regression analyses suggested a reduced infection risk was associated with a Vif-specific response Hazard Ratio = 0.36, 95% CI: 0.19 to 0.66. In pilot analyses of T cell activation, the frequency of CD38+HLA-DR+ CD8+ T cells was greater in those who seroconverted relative to those that remained uninfected (1.30% vs. 0.82%, respectively, P = 0.005). HLA-B15 showed the strongest association with infection outcomes among all others. HLA-B15 allele frequency in HESN was 0.0392 in HESN and 0.1961 in those who became infected. HLA-B15 and was also associated with lower T cell response frequency. PrEP studies provide the naturalistic setting to assess the immune fingerprint of HIV resistance in HESN, providing the right control group, sufficient subject numbers and clinical outcomes to associate infection risk. We found Vif-specific T cell responses and lower T cell activation was associated with reduced infection risk while Protease responses, greater frequencies of activated T cells, and having the HLA-B15 Class I MHC allele was associated with increased HIV infection risk.